2018
DOI: 10.1186/s40170-018-0185-4
|View full text |Cite
|
Sign up to set email alerts
|

Protein interaction and functional data indicate MTHFD2 involvement in RNA processing and translation

Abstract: BackgroundThe folate-coupled metabolic enzyme MTHFD2 is overexpressed in many tumor types and required for cancer cell proliferation, and is therefore of interest as a potential cancer therapeutic target. However, recent evidence suggests that MTHFD2 has a non-enzymatic function which may underlie the dependence of cancer cells on this protein. Understanding this non-enzymatic function is important for optimal targeting of MTHFD2 in cancer.MethodsTo identify potential non-enzymatic functions of MTHFD2, we defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 56 publications
0
29
0
Order By: Relevance
“…In addition to its known function in mitochondrial folate metabolism, Nina reported that MTHFD2 was able to enter the nucleus and co-localize with DNA replication sites [19], which further supports its important regulatory roles in tumorigenesis. Costas also demonstrated that MTHFD2 interacted with many nuclear proteins associated with RNA metabolism and translation [20]. Further studies are warranted to elucidate the molecular mechanisms for the tumor promoting role of MTHFD2 in HNSCC.…”
Section: Discussionmentioning
confidence: 95%
“…In addition to its known function in mitochondrial folate metabolism, Nina reported that MTHFD2 was able to enter the nucleus and co-localize with DNA replication sites [19], which further supports its important regulatory roles in tumorigenesis. Costas also demonstrated that MTHFD2 interacted with many nuclear proteins associated with RNA metabolism and translation [20]. Further studies are warranted to elucidate the molecular mechanisms for the tumor promoting role of MTHFD2 in HNSCC.…”
Section: Discussionmentioning
confidence: 95%
“… 12 , 13 In addition to its canonical role to facilitate one‐carbon metabolism for purine synthesis, recent studies characterize MTHFD2 with redox defence, epigenetic modification, RNA translation and DNA repair. 14 , 15 , 16 , 17 Knockdown of MTHFD2 in colorectal cancer hinders NADPH production and makes cancer cells more sensitive to oxidative stress. 14 In renal cell carcinoma, MTHFD2 promotes the mRNA methylation of HIF‐2α via metabolic reprogramming.…”
Section: Introductionmentioning
confidence: 99%
“…MTHFD2-associated mTOR signaling pathway might exert protective effects on neuronal development in LGG. There was related study which suggests the novel function of MTHFD2 in RNA metabolism and translation, identifying as a potential non-enzymatic functions [30]. It follows that MTHFD2 has the potential to play a significant role in LGG through various pathways.…”
Section: Discussionmentioning
confidence: 99%